2020
DOI: 10.12890/2020_001403
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella infection as a trigger for Polyarteritis Nodosa

Abstract: Polyarteritis nodosa is a systemic necrotizing vasculitis that typically affects medium-sized muscular arteries, with occasional involvement of small muscular arteries. Most cases of polyarteritis nodosa are idiopathic but multiple infectious agents have been associated with this disease. We present a clinical case of a 72-year-old male with fever, diarrhoea and haemodynamic instability, diagnosed with a bacterial infection caused by Salmonella Typhi. One week after clinical resolution of the infection, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Case reports exploring the linkage between NTS infection and vasculitis have been published. For example, Tavares et al proposed NTS infection as a possible trigger for the development of polyarteritis nodosa, a systemic necrotizing vasculitis (17). Additionally, Filiz et al reported a case of an interleukin 12 receptor beta 1 (IL-12Rb1) deficiency with cutaneous leukocytoclastic vasculitis due to Salmonella enteritidis infection (18).…”
Section: Introductionmentioning
confidence: 99%
“…Case reports exploring the linkage between NTS infection and vasculitis have been published. For example, Tavares et al proposed NTS infection as a possible trigger for the development of polyarteritis nodosa, a systemic necrotizing vasculitis (17). Additionally, Filiz et al reported a case of an interleukin 12 receptor beta 1 (IL-12Rb1) deficiency with cutaneous leukocytoclastic vasculitis due to Salmonella enteritidis infection (18).…”
Section: Introductionmentioning
confidence: 99%